War and Technology : A Very Short Introduction - Roland, Alex, 1944- (New York Oxford University Press, 2016)
Politics, economics, ideology, culture, strategy, tactics, and philosophy have all shaped war, but none of these factors has driven the evolution of warfare as much as technology. Expanding on this compelling thesis, this very short introduction traces the co-evolution of technology and war from the Stone Age to the age of cyberwar and nanotechnology.
Include Index
Keywords: Military Art and Science -- War